Diabetes mellitus is associated with higher risk of third degree atrioventricular block – a Danish nationwide registry study. (25th November 2020) - Haxha, S; Pedersen-Bjergaard, U; Philbert, B.T; Lindhardt, T.B; Hoejberg, S; Schjerning, A.M; Ruwald, M.H; Gislason, G.H; Torp-Pedersen, C; Bang, C.N
Abstract: Background: Diabetes mellitus (DM) is a risk factor for cardiovascular disease and sudden cardiac death. Increasing evidence shows that DM may be associated with electric disturbances including arrhythmias and atrioventricular block (AVB). However, the association of DM and AVB has never been confirmed in large studies. Purpose: The present study aims to determine the association of DM and third-degree AVB. Method: A nationwide nested case-control study of patients >40 years with third-degree AVB between 1995 and end of 2017, matched 1:2 on age and gender with controls from the Danish background population. DM was defined if patients were prescribed oral antidiabetics or insulin, or if they were diagnosed with an ICD10 code of DM type I or II. Data on medication, comorbidity, and outcomes were collected from Danish nationwide registries. Conditional logistic regression was used to estimate hazard ratio (HR) and 95% confidence intervals (95% CI) of third degree AVB. Results: Out of a total population of 8, 964, 086, we located a total of 32, 722 cases with third degree AVB, that were matched 1:2 with 65, 422 controls, with a mean age of 75.3 years and 59.1% males. The case group had more DM 18, 5% vs 13, 3%, acute myocardial infarction 27, 0% vs 16.0%, stroke 18.5% vs 16.2%, heart failure 20.0% vs 8.5% and chronic kidney disease 4.7% vs 2.5% compared to the control group. In multivariable analysis adjusted for comorbidities DM remained significantly associated with third degree AVB [HR 1.30 (95% CI: 1.25–1.35)] (Figure) Conclusion: In this nationwide population study, DM was associated with a higher risk of third degree AVB compared to matched controls without DM. This suggests a low threshold for use of ECG evaluation in case of dizziness or syncope in DM patients, and further, that ECG should be a part of routine controls of DM patients. Funding Acknowledgement: Type of funding source: None